2018
DOI: 10.1101/271148
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Efficient differentiation of vascular endothelial cells from dermal-derived mesenchymal stem cells induced by endothelial cell lines conditioned medium

Abstract: ObjectiveTo directionally-differentiate dermis-derived mesenchymal stem cells (DMSCs) into vascular endothelial cells (VECs) in vitro, providing an experimental basis for studies on the pathogenesis and treatment of vascular diseases.MethodsAfter separation by adherent culture, VEC line supernatant, vascular endothelial growth factor (VEGF), bone morphogenetic protein-4 and hypoxia were used for the differentiation of VECs from DMSCs. The cell type was authenticated by flow cytometry, matrigel angiogenesis ass… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…The VEGF release may accelerate cell migration (Mohsen, Hatef, Hamid, Ali, & Ghasem, ; Torio‐Padron et al, ). However, it seems that keeping VEGF in the scaffold supports vascularization because it not only enhances the proliferation of cells (Carpenter et al, ; Zhou et al, ), but also regulates the interaction between stem cells and ECs (such as directional differentiation of stem cells induced by ECs and pore size in the scaffold) and promotes angiogenesis (Adibfar et al, ; Cho, Moon, Park, Lee, & Seo, ; Zhou et al, ). Thus, in the present study, we designed two kinds of nanoparticles to load SDF‐1 and VEGF, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The VEGF release may accelerate cell migration (Mohsen, Hatef, Hamid, Ali, & Ghasem, ; Torio‐Padron et al, ). However, it seems that keeping VEGF in the scaffold supports vascularization because it not only enhances the proliferation of cells (Carpenter et al, ; Zhou et al, ), but also regulates the interaction between stem cells and ECs (such as directional differentiation of stem cells induced by ECs and pore size in the scaffold) and promotes angiogenesis (Adibfar et al, ; Cho, Moon, Park, Lee, & Seo, ; Zhou et al, ). Thus, in the present study, we designed two kinds of nanoparticles to load SDF‐1 and VEGF, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…To further verify that whether the effect of miR‐103 on the HFD‐induced atherosclerotic lesions in ApoE −/− mice was correlated with the PECAM‐1 + endothelial cells. First, PECAM‐1 + endothelial cells were sorted out using flow cytometry (Figure a; Zhou et al, ). RT‐qPCR (Figure b) revealed that miR‐103 expression in PECAM‐1 + endothelial cells of ApoE −/− mice fed a HFD were higher than that in PECAM‐1 + endothelial cells of ApoE −/− mice fed an ND.…”
Section: Resultsmentioning
confidence: 99%
“…However, there is a challenge to get effective induction of blood vessels into engineered graft in tissue engineering. The major obstacle is to obtain an abundant source of e cient autologous endothelial cells [25]. [29].…”
Section: Discussionmentioning
confidence: 99%